Perspectives about a meeting: dialogues between Paulo Freire and Hugues de Varine (Cadernos de Sociomuseologia, 2022)
The present work is a fragment of my master's thesis, which aims to present reflections on the relationship between the French consultant Hugues de Varine and the Pedagogue Paulo Freire. Something little elucidated in the analyzes of contemporary museological thought, which is expressed in the contributions that were produced during the period in which he was exiled in France. This friendship relationship produced issues involving the change in the theoretical paradigm of Museology, with the constitution of a new theoretical current focused on the issues debated at the Round Table in Santiago de Chile, in which the Brazilian dictatorial government prohibited the participation of Paulo Freire. The methodology used in this research was a bibliographic survey and interview analysis. Thus, the work raises the questioning of the search for what was inherited from the relationship between Freire and Varine, based on Odalice Miranda Priosti's systematization of what she understands as a "Liberation Museology" and the perception I make through the formatting in front of the Museology-Pedagogy-Theology triad. Through principles of a theory of liberation, which, in turn, is reverberated by the bibliographical production of Paulo Freire.Keywords: Liberation Museology, Hugues de Varine, Paulo Freire, Pedagogy, Theology.